Exploring Scarlett's Customer Loyalty: The Role of Purchase Decision as an Intervening Factor in the Context of Service and Product Quality - Jesslyn; Alfonsius (Universitas Pelita Harapan, 2024)
The surge in beauty industry competitors has led to a decline in Scarlett's ranking on e-commerce platforms. To enhance Scarlett's consumer loyalty, research on Scarlett's service quality and product quality is necessary. The interconnection among service quality, product quality, purchase decisions, and consumer loyalty is analyzed through corresponding indicators. This research includes 125 respondents. Data undergoes validity, reliability, classical assumption tests, and path analysis for advanced multiple linear regression analysis. The results demonstrate that Scarlett's service quality and product quality significantly influence purchase decisions. Additionally, Scarlett's service quality and product quality significantly influence customer loyalty. Purchase decision has an intervening factor on service quality and product quality towards customer loyalty. Improving Scarlett's service and product quality can elevate both consumer loyalty and purchase decisions.